Molecular Dynamic (MD) Simulations of Organic Modified Montmorillonite - Sylwia Cukrowicz; Paweł Goj; Paweł Stoch; Artur Bobrowski; Bożena Tyliszczak; Beata Grabowska (Applied Sciences, 2021)
This study complements the knowledge about organobentonites, which are intended to be new binders in foundry technology. In the developed materials, acrylic polymers act as mineral modifying compounds. Modification of montmorillonite in bentonite was carried out in order to obtain a composite containing a polymer as a lustrous carbon precursor. The polymer undergoes thermal degradation during the casting process, which results in the formation of this specific carbon form, ensuring the appropriate quality of the casting surface without negative environmental impact. The present paper reports the results of computational simulation studies (LAMMPS software) aimed at broadening the knowledge of interactions of organic molecules in the form of acrylic acid and acrylate anions (from sodium acrylate) near the montmorillonite surface, which is a simplified model of bentonite/acrylic polymer systems. It has been proven that the –COOH group promotes the adsorption of acrylic acid (AA) to the mineral surface, while acrylate ions tend to be unpredictably scattered, which may be related to the electrostatic repulsion between anions and negatively charged clay surfaces. The simulation results are consistent with the results of structural tests carried out for actual organobentonites. It has been proven that the polymer mainly adsorbs on the mineral surface, although it also partially intercalates into the interlayer spaces of the montmorillonite. This comprehensive research approach is innovative in the engineering of foundry materials. Computer simulation methods have not been used in the production of new binding materials in molding sand technology so far.